Pengembangan Media Infografiscandi Penataran Sebagai Sumber Sejarah Siswa Kelas VII di MTs Salafiyah Kasim Blitar - Ahmad Ahsan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Learning media is an important thing to do in learning, therefore researchers develop learning media. This research was conducted at MTs Salafiyah Kasim because this school has potential and problems. The problem that researchers found in class was the lack of student activity in participating in history learning in class, namely at the beginning of learning there were students who felt sleepy and apart from that other students preferred to play with their classmates, so students became less active in the material. From the results of these observations, the researcher obtained several problem formulations, namely 1.) What are the steps for developing infographic media on the theme of the upgrading temple for class VII students at Mts Salafiyah Kasim. 2.) What is the level of validity of developing infographic media on the theme of upgrading temples for class VII students at Mts Salafiyah Kasim. This research includes development research or R&D (Research and Development) using the ADDIE development model. Data collection by researchers uses observation, questionnaires and documentation. The data obtained will be in the form of qualitative and quantitative data. Qualitative data in the form of observations and short interviews and quantitative data in the form of test scores and results from validation of infographic media. The validity of infographic media on the theme of upgrading temples is in the good category. In the media expert validity test the average was 50 with a percentage of 83%, in the material expert validity test the average was 93 with a percentage of 88%. Based on these results, infographic media is suitable for use. Steps for developing infographic media on the theme of temple upgrading. In the first stage of analysis, the researcher analyzed the needs in consultation with the class VII social studies teacher at Mts Salafiyah Kasim, namely Ludfi ​​Abu Mahmud, S. Mat., in the second stage of design, the researcher designed the infographic media as attractively as possible , the third stage of development, the researcher validates the learning media with validators, the fourth stage of implementation, the researcher tests the media for large-scale and small-scale trials. The fifth stage of evaluation, comparison of trials of infographic media on a large scale and a small scale.